2022
DOI: 10.3390/coatings12060799
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Graphene Oxide on Polycaprolactone PCL Surfaces: Antimicrobial Activity and Osteogenic Differentiation of Mesenchymal Stem Cell

Abstract: In dentistry, bone regeneration requires osteoinductive biomaterial with antibacterial properties. Polycaprolactone (PCL) may be combined with different nanofillers including reduced graphene oxide (rGO). Here, the amount of rGO filler was defined to obtain a biocompatible and antibacterial PCL-based surface supporting the adhesion and differentiation of human mesenchymal stem cells (MSCs). Compounds carrying three different percentages of rGO were tested. Among all, the 5% rGO-PCL compound is the most bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…However, after 7 days of incubation, a slight proliferation was detected for the PCL-based composite filled with GO, whereas the composite filled with grafted with oligo(Glu) showed a more pronounced effect. Similar results on the proliferation of the hMSCs or MG-63 cells adhered to the surface of GO-containing PCL- or PLA-based composites over unfilled PCL were also reported in a number of studies [ 58 , 59 , 60 ]. Moreover, Scaffaro et al observed a higher number of cells over time when comparing PCL composites filled with neat GO and covalently PEGylated GO [ 61 ].…”
Section: Resultssupporting
confidence: 84%
“…However, after 7 days of incubation, a slight proliferation was detected for the PCL-based composite filled with GO, whereas the composite filled with grafted with oligo(Glu) showed a more pronounced effect. Similar results on the proliferation of the hMSCs or MG-63 cells adhered to the surface of GO-containing PCL- or PLA-based composites over unfilled PCL were also reported in a number of studies [ 58 , 59 , 60 ]. Moreover, Scaffaro et al observed a higher number of cells over time when comparing PCL composites filled with neat GO and covalently PEGylated GO [ 61 ].…”
Section: Resultssupporting
confidence: 84%
“…The study presented by Letizia Ferroni et al [ 61 ] investigated the creation and evaluation of rGO-PCL (reduced graphene oxide-polycaprolactone) composites for possible use in bone tissue engineering. Evaluation of the antibacterial efficacy of the composites against various bacterial strains revealed that they had a bacteriostatic effect on Gram-positive bacteria, particularly the 5% rGO-PCL composite.…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity and mineral matrix deposition were found to be maximal on the surface of 5% rGO-PCL, indicating better osteogenic differentiation capacity, and the expression of osteogenic markers such as OPN, OCN, RUNX2, and osterix (OSX) was found to be high on the surface of 5% rGO-PCL, indicating excellent osteoblastic proliferation. Certainly, therefore, the 5% rGO-PCL composite has proven to be a viable option for creating improved biomaterials for bone regeneration due to its demonstrated biocompatibility, bacteriostatic action against Gram-positive bacteria, and ability to enhance osteogenic differentiation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the temporal control of graphene properties has been proposed in in vitro applications for diagnostic purpose, 31,32 to control mechanical properties of scaffolds 33 or to control cell or drug release [34][35][36] rather than modulating cell attachment and biofouling on scaffolds. Composites of graphene derivatives and PCL have also been studied; however, frequently, GO has been reduced to rGO to allow for proper mixing with PCL 37 since GO is poorly soluble in organic solvents compared to rGO and might result in non-uniform composites. 38,39 In our work, the presence of alkylamine groups is used not only to enhance the dispersibility of GO in organic solvents but also to control surface hydrophobicity during contact with biological fluids.…”
Section: Introductionmentioning
confidence: 99%